2016
DOI: 10.3389/fnsys.2016.00086
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Visual Callosal Connections Following Alterations of Retinal Input and Brain Damage

Abstract: Vision is a very important sensory modality in humans. Visual disorders are numerous and arising from diverse and complex causes. Deficits in visual function are highly disabling from a social point of view and in addition cause a considerable economic burden. For all these reasons there is an intense effort by the scientific community to gather knowledge on visual deficit mechanisms and to find possible new strategies for recovery and treatment. In this review, we focus on an important and sometimes neglected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 161 publications
1
18
0
Order By: Relevance
“…Therefore down-regulation of interhemispheric tracts could affect a variety of visual functions including those known to be disrupted by early life enucleation such as face perception and motion integration. Our results are consistent with a large literature involving non-human animals demonstrating that a range of manipulations including early monocular enucleation or eyelid suture alter the development of intracortical primary visual cortex connections (Nys et al, 2015, Restani & Caleo, 2016.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore down-regulation of interhemispheric tracts could affect a variety of visual functions including those known to be disrupted by early life enucleation such as face perception and motion integration. Our results are consistent with a large literature involving non-human animals demonstrating that a range of manipulations including early monocular enucleation or eyelid suture alter the development of intracortical primary visual cortex connections (Nys et al, 2015, Restani & Caleo, 2016.…”
Section: Discussionsupporting
confidence: 91%
“…Reduced FA is consistent with increased RD and MD, although FA is a more general measure of white matter microstructure . Intracortical connectivity within the normal visual pathway facilitates binocular vision, enables integrated processing across the left and right visual hemifields (Peiker, Wunderle, Eriksson, Schmidt & Schmidt, 2013, Restani & Caleo, 2016, Song & Rees, 2018 and facilitates interhemispheric synchronization that supports sparse encoding of visual information (Knyazeva, 2013). Therefore down-regulation of interhemispheric tracts could affect a variety of visual functions including those known to be disrupted by early life enucleation such as face perception and motion integration.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence about restructuring of callosal connections following cortical damage in humans and animals is compelling ( 46 ). We speculate that the functional meaning of interhemispheric communication at posterior callosal sites is that of transferring sensory-based information.…”
Section: Discussionmentioning
confidence: 99%
“…Commissural connections participate in processing and integration of information between two hemispheres (Restani and Caleo, 2016 ). It was reported that two of prostriata's adjoining areas, PrS and PaS, have strong commissural connections with contralateral medial entorhinal cortex (MEC) in rat (van Groen and Wyss, 1990 ; Honda et al, 2008 ; Preston-Ferrer et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%